Brandsplaining: Why Marketing is (Still) Sexist and How to Fix It - Cunningham, Jane (Penguin Random House UK, 2024)
Brands profit by telling women who they are and how to be. Now they've discovered feminism and are hell bent on selling 'fempowerment' back to us. But behind the go-girl slogans and the viral hash-tags has anything really changed